The acquisition of rhotics in onset clusters in L2 Spanish - Carolina González; Christine Weissglass (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
This study examines the acoustic realization of rhotics in Spanish onset clusters in 10 native speakers and 25 second language learners (L2) with English as their L1. The comparison of rhotic manner, duration, and svarabhakti vowel occurrence shows partial evidence of English transfer in the L2 group, since fricative, retroflex approximant and coarticulated variants, common in English, account for almost 40% of realizations. Rhotics are also longer in the L2 group and svarabhakti vowels less frequent. Results also show that stop voicing and place of articulation impact rhotic realization in the L2 group. The examination of individual patterns shows that some L2 learners are in initial stages of rhotic acquisition, while others are approaching the native pattern.